2022
DOI: 10.25165/j.ijabe.20221506.7137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil mechanical properties on the height and tractive performance of rubber grouser at different moisture contents

Abstract: Rubber tracked vehicles are commonly used on agricultural machinery that perform agricultural operations such as rice harvesting in soft paddy fields with low bearing capacity. Research was carried out to assess the influence of soil moisture content and mechanical properties on the tractive performance of a rubber grouser with three heights (45 mm, 55 mm, 60 mm). The direct shear test and penetration test were used in this study, which was based on a semi-empirical approach of determining tractive parameters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, fluctuations in soil hydraulic conductivity were found to be associated with the first 10 years of restoration (Ren et al 2016). Previous studies have shown that soil moisture is closely related to soil physical properties such as infiltration performance, particle size distribution, and pore condition (Shaikh et al 2022;Yuan et al 2020) An other former studies reported that plant physiological parameters also very important because these parameters directly or indirectly its effect on soil physical properties (Solangi et al 2021;Tunio et al 2020). Salt sress also important factor which change the soil physical properties (Ali ).…”
mentioning
confidence: 95%
“…However, fluctuations in soil hydraulic conductivity were found to be associated with the first 10 years of restoration (Ren et al 2016). Previous studies have shown that soil moisture is closely related to soil physical properties such as infiltration performance, particle size distribution, and pore condition (Shaikh et al 2022;Yuan et al 2020) An other former studies reported that plant physiological parameters also very important because these parameters directly or indirectly its effect on soil physical properties (Solangi et al 2021;Tunio et al 2020). Salt sress also important factor which change the soil physical properties (Ali ).…”
mentioning
confidence: 95%
“…They facilitate controlled experiments, illuminating the interplay between various soil factors like type, density, and moisture content. Pioneering studies, such as those by Shaikh et al [9] and Oh et al [10], have harnessed soil bins to understand the profound effects of soil moisture content and soil compaction, respectively, on pressure sinkage and bearing capacity in the context of tracked vehicles. However, despite the wealth of knowledge derived from these studies, a gap remains in the realm of real-world field tests.…”
Section: Introductionmentioning
confidence: 99%